Electronic spectroscopy of differential mobility-selected prototropic isomers of protonated para-aminobenzoic acid. Issue 36 (10th September 2021) - Coughlan, Neville J. A.; Fu, Weiqiang; Guna, Mircea; Schneider, Bradley B.; Le Blanc, J. C. Yves; Campbell, J. Larry; Hopkins, W. Scott
Abstract : Differential mobility spectrometry is used to separate prototropic isomers of para -aminobenzoic acid prior to laser spectroscopic investigation. Abstract : para -Aminobenzoic acid (PABA) was electrosprayed from mixtures of protic and aprotic solvents, leading to formation of two prototropic isomers in the gas phase whose relative populations depended on the composition of the electrospray solvent. The two ion populations were separated in the gas phase using differential mobility spectrometry (DMS) within a nitrogen-only environment at atmospheric pressure. Under high-field conditions, the two prototropic isomers eluted with baseline signal separation with the N -protonated isomer having a more negative CV shift than the O -protonated isomer, in accord with previous DMS studies. The conditions most favorable for formation and separation of each tautomer were used to trap each prototropic isomer in a quadrupole ion trap for photodissociation action spectroscopy experiments. Spectral interrogation of each prototropic isomer in the UV region (3–6 eV) showed good agreement with previously recorded spectra, although a previously reported band (4.8–5.4 eV) was less intense for the O -protonated isomer in our measured spectrum. Without DMS selection, the measured spectra contained features corresponding to both protonated isomers even when solvent conditions were optimised for formation of a single isomer. Interconversion between protonated isomers within the ion trap was observed when protic ESI solvents were employed, leading to spectral cross contamination even with mobility selection. CCSD vertical excitation energies and vertical gradient (VG) Franck–Condon simulations are presented and reproduce the measured spectral features with near-quantitative agreement, providing supporting evidence for spectral assignments.